PERSEPSI IBU TENTANG IMUNISASI HPV PADA ANAK UNTUK PENCEGAHAN KANKER SERVIKS - Debi Novita Siregar; Sunarti Sunarti (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2020)
Cervical cancer is the number two cause of death of women in the world. Cervical cancer that affects 70% of women is caused by HPV virus types 16 and 18. So that prevention of cervical cancer can be done by administering HPV immunization. The success rate in giving HPV immunization can reach 100% if given as much as 2 times in children aged 9-15 years and has never been infected with HPV. This study aims to determine the perception of mothers about HPV immunization in children for the prevention of cervical cancer early in the District of East Medan. The study used a qualitative design with a phenomenological approach. Informants in the study were 33 mothers. Data collection in this study uses interview techniques. The results showed that mothers had positive perceptions about HPV immunization, where after interviews were obtained 30 (90.9%) mothers had positive perceptions about HPV immunization and 3 (9.09%) mothers had negative perceptions about HPV immunization in children for prevention of cervical cancer. Conclusion The mother has a positive perception where there are four themes that influence the mother's perception of HPV immunization in children for cervical cancer prevention, namely information, government participation, content and costs of HPV immunization